Monty Hall game: a host with limited budget - Alvarez, Agustin (2014)
In this paper we introduce a new version of the classical Monty Hall problem, where the host is trying to maximize the audience while is restricted in its budget. This problem is related to the design of games with a predetermined outcome, and decision making process under uncertainty when the agent does not know if the received advice is favorable or not.